School Library Professionals Report Inadequate Student Digital Information Literacy Across Global Contexts - McCrary, Quincy D. (Evidence Based Library and Information Practice, 2025)
A Review of: Merga, M. K., & Mat Roni, S. (2025). School library professionals' perceptions of students' digital information literacy. Journal of Library Administration, 65(4), 397–411. https://doi.org/10.1080/01930826.2025.2475701 Objective – To explore school library professionals' perceptions of their students' digital information literacy (DIL) knowledge, skills, and learning opportunities across multi-country contexts. Design – Cross-sectional survey questionnaire. Setting – School library professionals (SLPs) working in 63 countries. Four public libraries in Norway: The Northern and central-Eastern regions (2), and Oslo (2). Subjects – 971 SPLs responded to the survey, of which 801 (82.5%) were included in the analysis as they indicated they were knowledgeable about their students’ DIL. Methods – Data was collected via an online Qualtrics-hosted survey from July 12 to August 29, 2024. This analysis focused on one block of questions within a larger international survey of SLPs (Merga & Mat Roni, 2025, p. 401). The DIL measurement included 12 Likert-scale items determining access to technology, DIL education provision, and students' DIL skills. The researchers conducted partial correlation tests and regression analyses, controlling for country income level. A three-step mediation analysis with Sobel test examined the role of school libraries in DIL instruction. The survey instrument underwent cognitive piloting with diverse international SLPs to ensure cross-contextual validity. Main Results – The findings revealed that although technological infrastructure was nearly universal (95.1% reported majority internet access at country level), and DIL instruction was reportedly integrated across all schooling years in most schools (75.8%), fewer than half of SLPs perceived DIL development as a priority at their schools, with even fewer (48.8%) noting it was prioritized at the national level. The respondents perceived students' DIL skills as low, with only 43.7% of SLPs agreeing that students have strong DIL skills for their age. Even fewer SLPs believed students possessed sound strategies for evaluating online information credibility (34.2%) or expertise (27.8%). The data revealed a moderate positive correlation (r = .56, p < .001) between DIL instruction and perceived student DIL skills. Conclusion – While many respondents reported that technological infrastructure was widely available, the authors emphasize that global internet access remains uneven, with only 57% of the population reliably connected. Findings should therefore be interpreted with these disparities in mind. The authors recommend greater prioritization of DIL instruction in schools. They also suggest an increased utilization of SLPs (and school libraries) who possess unique qualifications for DIL education but remain underutilized in 35% of contexts.